2007
DOI: 10.1590/s1413-70542007000400009
|View full text |Cite
|
Sign up to set email alerts
|

Determinação da variabilidade em isolados de Colletotrichum lindemuthianum por meio de marcadores morfológicos e culturais

Abstract: RESUMOColletotrichum lindemuthianum (teleomorfo Glomerella cingulata f. sp. phaseoli) apresenta ampla variabilidade genética, demonstrada por suas características morfológicas. Com este trabalho, objetivou-se caracterizar, por meio de marcadores morfológicos, diferentes isolados de C. lindemuthianum e identificar marcadores morfológicos com uso potencial em análises genéticas. Foram avaliados os seguintes caracteres morfológicos e culturais: cor e textura das colônias, compatibilidade vegetativa e sexual, índi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
2
9
0
1
Order By: Relevance
“…isolates into the groups formed in the tree was mainly due to the colony diameter characteristic. Souza et al (2007) identified the shape of Colletotrichum lindemuthianum conidia as a morphological marker that could be used for genetic analyses; Alves et al (2008) studied a collection of isolates, identified as Lasiodiplodia theobromae, and potential cryptic species based on differences in conidial morphology and on sequence data from the ITS regions and EF1-α gene; and Jeewon et al (2004) reported that, for Pestalotiopsis species, the pigmentation of median cells and morphology of apical appendages are the most import characters to distinguish groups. These reports corroborate the studies of Wei & Xu (2004) and Liu et al (2007), who used morphological characters as markers for species or isolate differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…isolates into the groups formed in the tree was mainly due to the colony diameter characteristic. Souza et al (2007) identified the shape of Colletotrichum lindemuthianum conidia as a morphological marker that could be used for genetic analyses; Alves et al (2008) studied a collection of isolates, identified as Lasiodiplodia theobromae, and potential cryptic species based on differences in conidial morphology and on sequence data from the ITS regions and EF1-α gene; and Jeewon et al (2004) reported that, for Pestalotiopsis species, the pigmentation of median cells and morphology of apical appendages are the most import characters to distinguish groups. These reports corroborate the studies of Wei & Xu (2004) and Liu et al (2007), who used morphological characters as markers for species or isolate differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…The Colletotrichum genus exhibits wide genetic variability and, in addition to sexual recombination, other mechanisms such as the parasexual cycle exist that allow the transfer of genetic material (Castro-Prado et al, 2007) and asexual recombination through conidial anastomosis tubes (CATs) (Roca et al, 2003;Ishikawa et al, 2012). High variability has been observed in morphological and physiological traits, and several of these are important for pathogen development and survival, such as mycelial growth rate, colony diameter, sporulation capacity, and percent germination (Souza et al, 2007). Another important trait used in taxonomy of the genus Colletotrichum is the cytology of the conidia and the presence of septa in the germinated conidia, the latter of which is an important morphological marker (Souza et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…High variability has been observed in morphological and physiological traits, and several of these are important for pathogen development and survival, such as mycelial growth rate, colony diameter, sporulation capacity, and percent germination (Souza et al, 2007). Another important trait used in taxonomy of the genus Colletotrichum is the cytology of the conidia and the presence of septa in the germinated conidia, the latter of which is an important morphological marker (Souza et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cinco dias após a aplicação do patótipo virulento (Sicard et al,1997;Souza et al, 2007), e a indução da resistência das plantas é uma forma de garantir que a resistência não seja quebrada por um período maior de tempo. Também foi observada interação dos tratamentos na redução da severidade da doença.…”
Section: Três Dias Após a Inoculaçãounclassified